(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Startups in India face a range of finance-related challenges that can hinder their growth and sustainability. Key issues include limited access to capital, complex regulatory compliance, high operational costs, inadequate financial planning, and limited financial literacy among founders. Additionally, the fragmented funding ecosystem and difficulty in securing timely credit from traditional financial institutions further exacerbate these problems. To overcome these challenges, startups can explore alternative funding sources such as venture capital, angel investors, government schemes, and crowdfunding. Strengthening financial management skills, leveraging fintech solutions, and ensuring compliance with regulatory frameworks are also critical steps. This article explores these challenges in detail and provides strategic insights and practical solutions to help Indian startups navigate financial hurdles and build resilient, scalable businesses.